A‐shaped wideband dielectric resonator antenna for wireless communication systems and its MIMO implementation. Issue 8 (18th April 2018) - Sharma, Abhishek; Sarkar, Anirban; Biswas, Animesh; Akhtar, M. Jaleel
Abstract: In this article, a new A‐shaped dielectric resonator antenna (DRA) excited by a conformal strip is proposed for wideband applications. The wide bandwidth is achieved by combining two adjacent modes that is, TM101 and TM103 . The experimental results demonstrate that the proposed DRA offers an impedance bandwidth (for S11 ≤ −10 dB) of 59.7% (3.24‐6.0 GHz), covering IEEE 802.11 and U‐NII bands. The antenna provides a fairly stable radiation pattern with the gain ranging from 5.29 to 7 dBi across the operating bandwidth. A dual‐element multiple‐input multiple‐output (MIMO) system is also realized using the proposed wideband DRA. The impedance bandwidth of the dual‐element MIMO antenna is 59.2% and 60.9% for Port1 and Port2, respectively and the isolation between the ports is better than 20 dB across the bandwidth. For Port1, the gain of the MIMO antenna ranging from 6.03 to 7.45 dBi is obtained across the bandwidth. Furthermore, the diversity performance of the MIMO antenna is found to be good with envelope correlation coefficient below 0.003 over the operating band. The proposed antenna could be the potential candidate for worldwide interoperability for microwave access (WiMAX), wireless local area network (WLAN) and lower European UWB frequency band (3.4‐5.0 GHz) applications.